Edukasi Menarik Pencegahan Stunting dan Pemanfaatan Aplikasi E-Posyandu dalam Monitoring Gizi Anak - Hiswara, Abrar; Soliha, Amalia Nur; Purba, Daud Tri Bakti; Octaviana, Dika Aditya; Hendrianto, Fendy; Himawan, Haris; Kesuma, Kaylista Nabila Nastiti; Assyidqi, Muhamad Salam; Agustyan, Muhammad Dafa; Kamil, Mumtaz Abdurrahman; Kamil, Mumtaz Abdurrahim (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Posyandu is the main forum for monitoring nutritional status and preventing stunting in infants and toddlers. Stunting is a condition where growth is inhibited in children due to lack of nutritional intake for a long time because food intake is not in accordance with nutritional needs. Maternal nutrition plays a major role in preventing stunting in children from an early age. In addition to growth problems, stunting also affects children's intelligence levels and learning abilities. Kuliah Kerja Nyata (KKN) is a community service program that provides opportunities for students to apply the knowledge and skills gained on campus directly in the community. Through Real Work Lecture (KKN) activities as a student community service program, it aims to socialize the dangers of stunting on children's growth and development, and socialize how to prevent stunting. In addition, this activity is also carried out to conduct counseling to the community about a healthy menu with balanced nutrition which aims to provide an understanding of the importance of regulating nutrition in the food given to children. This Real Work Lecture (KKN) activity can be a forum to provide understanding and education in an interesting way about the dangers of stunting.